2018
DOI: 10.1097/01.nep.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Shift From Brick and Mortar: Full-Time Nursing Faculty Off Campus

Abstract: The organizational structure for the Master of Science in Nursing's online program at Sacred Heart University offers a remarkably different innovative faculty model. Full-time, doctorally prepared faculty reside in several different states and teach online but are fully integrated and immersed in all aspects of the college of nursing. This untraditional model, which has proven to be successful over time using best practices for online education, is replicable and offers an innovative option for online learning. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…27 Collaborative learning supports the academic socialization process and facilitates the sense of social presence in the classroom environment. 28,29 For students enrolled in traditional settings, social and academic integration can occur more seamlessly. The goal of the Let's Check-In: Tips for Success approach was to develop a distance learning community, where students would become active participants in their learning process, synonymous with experiences in a traditional classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Collaborative learning supports the academic socialization process and facilitates the sense of social presence in the classroom environment. 28,29 For students enrolled in traditional settings, social and academic integration can occur more seamlessly. The goal of the Let's Check-In: Tips for Success approach was to develop a distance learning community, where students would become active participants in their learning process, synonymous with experiences in a traditional classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying additional platforms and technology to enhance engagement between students and faculty allows for the development of the distance learning community 27. Collaborative learning supports the academic socialization process and facilitates the sense of social presence in the classroom environment 28,29. For students enrolled in traditional settings, social and academic integration can occur more seamlessly.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, medical research has shown that cerebrovascular events' timing is closely related to the circadian rhythm of human blood pressure [7]. With the birth and development of time medicine and its penetration and promotion of nursing discipline, today's nursing model has been derived, and time nursing has begun to attract scholars' attention [8][9][10][11][12]. So far, many kinds of regression models have been established for continuous measurement of blood pressure, among which pulse wave velocity (PWV) is the most common.…”
Section: Introductionmentioning
confidence: 99%